INJURY PROFILE OF BRAZILIAN ATHLETES IN OLYMPIC GAMES 2012. Issue 7 (11th March 2014) - Bolling, C; Leite, M; Neto, JG; Barreto, H; Tadiello, F; Medeiros, L; Rodrigues, F
Abstract : Background: Athletes performance in Olympic Games depends on health condition. Physiotherapy staff treats injuries, relieves pain and manages symptoms to help athletes to reach the highest performance. Objetive: To describe injury profile of athletes treated in Physiotherapy department in London Olympic Games 2012. Design: This is a descriptive epidemiological study about injuries in Olympic Games. Setting: This study was conducted by Brazilian delegation physiotherapists during the Olympic Games in London 2012. Participants: All athletes (n=132) treated in physiotherapy department of Brazilian Olympic committee. Intervention: All brazilian delegation athletes could request for health care in the physiotherapy department. Physiotherapists reported all injuries and interventions in a standard form. Main outcome measurements: The information collected was: name, gender, modality, number of sessions; related to injuries: location, type, cause, mechanism, symptoms duration. The data analyses was descriptive. Results: 132 athletes (72 men/60 women) were treated in 680 treatment sessions with a mean of 5.15 session/injury. Injuries distribution related to modality was: boxe (13.9%), volleyball (13.9%), basketball (12.2%), handball (11.4%), gymnastics (7, 3%), judo (6.5%), athletics (5.7%), swimming (5.7%), sailing (5.7%), others (14.7%). Injuries occurred in lower limbs (55.3%), upper limbs (22.7%), trunk (19, 6%), others (2, 4%). The tendinopathies (29%) and muscular injuries (31%) were the most common type. Most frequent injury cause was overuse (73%) followed by contact injuries (14%). The majority of injuries had more than 4 months duration (33%), followed by 1–7 days duration (24%) and 8–30 days (12%). According to mechanism, 30% was traumatic injuries. Conclusion: The high number of overuse, tendinopathies and long term injuries indicate that many athletes arrived injured at Olympic games. Therefore a preventive strategy for chronic conditions should be a priority in Pre-Olympic training.